ELECTRICAL & ELECTRONIC ENGINEERING : THEORY AND APPLICATION SERIES 5: MICROLECTRONIC, MEDICAL ELECTRONIC AND IMAGE RETRIEVAL - Siti Zarina Mohd Muji; Rahmat Sanudin (Penerbit UTHM, 2017)
This book is the fifth of a books series produced by the Faculty of Electrical and Electronic Engineering (FKEE), Universiti Tun Hussein Onn Malaysia (UTHM). This book is the result of research and development as well as research conducted by the staff of FKEE. It can guide other researchers to improve their knowledge in the field of research, particularly in the area of Electrical and Electronic Engineering. There are five chapters in this book under computer engineering, microelectronic and biomedical field. All the topics discussed from basic to help readers understand easily. This book is suitable for university students and researchers also fans of Electrical Engineering courses to enhance their knowledge. Undergraduate students can get a rough idea about certain topics that may be useful for their study and a final year project. Postgraduate students may find this book to help them in getting new knowledge that will be used as input to their research. While the fans can carry out certain techniques in this book to create an innovative project. Therefore, this book should be part of the reference for everyone in the field of Electrical Engineering to guide and improve their knowledge. It is our hope that this booklet is able to produce a smart idea to all readers.